Adsorption of fluoroquinolone antibiotics from water and wastewater by colemanite - HACIOSMANOĞLU, GÜL GÜLENAY (My University, 2023)
© 2023 by the authors.Pharmaceutical residues in water and wastewater have become a worldwide problem with environmental and public health consequences. Antibiotics are of special importance because of the emergence of antibiotic-resistant genes. This study evaluates the adsorptive removal of four common fluoroquinolone antibiotics by using natural colemanite as an alternative adsorbent for the first time. Batch adsorption experiments were conducted for the mixture of fluoroquinolones as well as for individual compounds during the isotherm studies. Adsorption kinetic results indicated that the process followed the pseudo-second-order (PSO) model, while the Langmuir model described the sorption isotherms. The effects of pH and temperature on adsorption performance were determined, and the results indicated that the adsorption was endothermic and spontaneous, with increasing randomness at the solid–liquid interface. The effects of real water and wastewater matrices were tested by using tap water, surface water, and wastewater samples. Reusability experiments based on five adsorption–desorption cycles indicated that the adsorption performance was mostly retained after five cycles. The adsorption mechanism was elucidated based the material characterization before and after adsorption. The results indicate that colemanite can be used as an effective and reusable adsorbent for fluoroquinolone antibiotics as well as for other pollutants with similar physicochemical properties.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Health Sciences; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Mühendislik; Farmakoloji ve Toksikoloji; Sosyal Bilimler Genel; MÜHENDİSLİK, ÇEVRE; TOKSİKOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); Social Sciences (SOC); ENGINEERING; PHARMACOLOGY & TOXICOLOGY; SOCIAL SCIENCES, GENERAL; ENGINEERING, ENVIRONMENTAL; TOXICOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Kirlilik; Fizik Bilimleri; Halk, Çevre ve İş Sağlığı; Sağlık, Toksikoloji ve Mutajenez; Pollution; Physical Sciences; Public Health, Environmental and Occupational Health; Health, Toxicology and Mutagenesis; adsorption; colemanite; fluoroquinolone antibiotics; wastewater; water